2019
DOI: 10.1039/c9na00107g
|View full text |Cite
|
Sign up to set email alerts
|

The supramolecular structure and van der Waals interactions affect the electronic structure of ferrocenyl-alkanethiolate SAMs on gold and silver electrodes

Abstract: Understanding the influence of structural properties on the electronic structure will pave the way for optimization of charge transport properties of SAM devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 101 publications
1
17
0
Order By: Relevance
“…Peak IV originates from the transition to σ* of the C–H/C–S bonds, as discussed in our earlier NEXAFS results of Au–S(CH 2 ) 11 Fc SAMs. 56 The peak assignments from the periodic DFT molecule–metal calculations are generally consistent with previous assignments from gas-phase models of S–(CH 2 ) n –Fc–(CH 2 ) 13– n molecules bound to a single Au metal atom used in our previous study. 57 …”
Section: Results and Discussionsupporting
confidence: 86%
“…Peak IV originates from the transition to σ* of the C–H/C–S bonds, as discussed in our earlier NEXAFS results of Au–S(CH 2 ) 11 Fc SAMs. 56 The peak assignments from the periodic DFT molecule–metal calculations are generally consistent with previous assignments from gas-phase models of S–(CH 2 ) n –Fc–(CH 2 ) 13– n molecules bound to a single Au metal atom used in our previous study. 57 …”
Section: Results and Discussionsupporting
confidence: 86%
“…Organic self-assembled monolayers (SAMs) formed on semiconductor, metal or metal oxide surfaces are an integral component of molecular electronic devices, for electrical insulation, charge storage, and charge transport. A recent series of investigations of the charge transport properties of large-area, solid-state tunnel junctions comprised of SAMs of the redox-active ferrocenyl­alkanethiolates (Fc­(CH 2 ) n S) , or insulating n -alkanethiolates (CH 3 (CH 2 ) n S) have sparked renewed interest in the odd–even (or parity) effect, which refers to the alternation of a material’s structure and/or property due to an odd or even number of repeat units in the molecule. Parity effects in solid condensed phases often arise from differences in the intermolecular interactions and molecular packing.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the electronic properties of both the functional units and the electrodes, as well as the anchor groups, should be taken into consideration when choosing the number of methylene groups to control the interface coupling, thus resulting in variation of the methylene number among different systems. [ 37–39 ] In the second aspect, we found that the relative HOMO and LUMO resonance alignment among four single‐molecule junctions displayed an odd–even effect. This finding is similar to previous reports, where the structural odd–even behaviors led to electronic odd–even effects in either ferrocene−electrode coupling [ 38 ] or molecular rectification [ 40 ] of ferrocenyl‐alkanethiolate self‐assembled monolayers.…”
Section: Resultsmentioning
confidence: 91%
“…[ 37–39 ] In the second aspect, we found that the relative HOMO and LUMO resonance alignment among four single‐molecule junctions displayed an odd–even effect. This finding is similar to previous reports, where the structural odd–even behaviors led to electronic odd–even effects in either ferrocene−electrode coupling [ 38 ] or molecular rectification [ 40 ] of ferrocenyl‐alkanethiolate self‐assembled monolayers. While odd–even conductance variation was previously observed in carbon atomic wires [ 41 ] and n‐alkanes [ 42 ] when the length of the transport junction was increased, here the odd–even effect is regarding to the FMO alignment going from AM0‐DPP to AM3‐DPP.…”
Section: Resultsmentioning
confidence: 99%